2003
DOI: 10.1046/j.1365-3032.2003.00325.x
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional anoxia resistance in larval tiger beetle, Phaeoxantha klugii (Coleoptera: Cicindelidae)

Abstract: The tiger beetle Phaeoxantha klugii inhabits Central Amazonian floodplains, where it survives the annual inundation period in the third-instar larval stage submerged in the soil at approximately 29 C for up to 3.5 months. Because flooded soils quickly become anoxic, these larvae should be highly resistant to anoxia. The survival of adult and larval P. klugii was therefore tested during exposure to a pure nitrogen atmosphere in the laboratory at 29 C. Adult beetles were not resistant (< 6 h). Survival of larvae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 20 publications
(35 reference statements)
1
18
2
Order By: Relevance
“…Insects respond to the condition of hypoxia through various strategies such as reduction of metabolic and respiratory rates, and the reduction of the production of ATP. This process causes a decrease in locomotor movements of insects (Hoback et al 2000;Zerm & Adis 2003), as observed during this experiment. It is likely therefore that the condition of hypoxia influenced the respiratory rate, affecting the production of ATP, decreasing the motor activity of N. eichhorniae individuals submerged for short periods in previously boiled water and for periods longer than eight hours in natural non-aerated water.…”
Section: Discussionsupporting
confidence: 71%
“…Insects respond to the condition of hypoxia through various strategies such as reduction of metabolic and respiratory rates, and the reduction of the production of ATP. This process causes a decrease in locomotor movements of insects (Hoback et al 2000;Zerm & Adis 2003), as observed during this experiment. It is likely therefore that the condition of hypoxia influenced the respiratory rate, affecting the production of ATP, decreasing the motor activity of N. eichhorniae individuals submerged for short periods in previously boiled water and for periods longer than eight hours in natural non-aerated water.…”
Section: Discussionsupporting
confidence: 71%
“…The degree of flooding largely explains which strategy may evolve. For example, species that inhabit places that experience prolonged flooding events are more likely to exhibit physiological tolerance (Zerm and Adis 2003) or relocation (Brust et al 2006), presumably because plugging would not be sufficient over a long time. In locations that experience only short-term flooding caused by periodical rain, plugging in response to high soil moisture would be sufficient for the larvae to protect themselves against asphyxiation.…”
Section: Discussionmentioning
confidence: 99%
“…To survive flooding, tiger beetles that inhabit floodplains, such as Cicindela togata (Hoback et al 1998) and Phaeoxantha klugii (Zerm and Adis 2003), have evolved physiological tolerance to anoxia, and can survive many days of immersion. Some species show behavioral adaptation; for example Cicindela hirticollis larvae abandon their burrows and relocate in response to flooding (Brust et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Tiger beetle larvae are known to survive in water edge habitats that have been fully submerged for periods of 1-2 weeks or more (Hamilton, 1885;Willis, 1967;Wilson, 1974), but recent laboratory drowning studies with C. hirticollis found that most larvae survived less than 4 days and none longer than 8 days (Brust et al, 2005). Laboratory tests of Phaeoxantha klugi, a tiger beetle of the Amazonian floodplain, found that larvae could survive much longer (an average of 26 days) when placed in sediments for several weeks before becoming gradually flooded (Zerm and Adis, 2003). In particular, Zerm and Adis (2003) speculated that the increased survival resulted from metabolic depression caused by the gradual flooding which these beetles experience in their native habitat.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory tests of Phaeoxantha klugi, a tiger beetle of the Amazonian floodplain, found that larvae could survive much longer (an average of 26 days) when placed in sediments for several weeks before becoming gradually flooded (Zerm and Adis, 2003). In particular, Zerm and Adis (2003) speculated that the increased survival resulted from metabolic depression caused by the gradual flooding which these beetles experience in their native habitat. A recent study with C. hirticollis, however, found that larvae within their closed burrows in laboratory chambers responded to flooding by readily digging out of their burrows and floating to the water surface (Brust et al, 2006).…”
Section: Discussionmentioning
confidence: 99%